Targeting mitochondria by Zn(II)N-alkylpyridylporphyrins: the impact of compound sub-mitochondrial partition on cell respiration and overall photodynamic efficacy. - Ahmad M Odeh; James D Craik; Rima Ezzeddine; Artak Tovmasyan; Ines Batinic-Haberle; Ludmil T Benov (PLoS ONE, 2014)
Mitochondria play a key role in aerobic ATP production and redox control. They harness crucial metabolic pathways and control cell death mechanisms, properties that make these organelles essential for survival of most eukaryotic cells. Cancer cells have altered cell death pathways and typically show a shift towards anaerobic glycolysis for energy production, factors which point to mitochondria as potential culprits in cancer development. Targeting mitochondria is an attractive approach to tumor control, but design of pharmaceutical agents based on rational approaches is still not well established. The aim of this study was to investigate which structural features of specially designed Zn(II)N-alkylpyridylporphyrins would direct them to mitochondria and to particular mitochondrial targets. Since Zn(II)N-alkylpyridylporphyrins can act as highly efficient photosensitizers, their localization can be confirmed by photodamage to particular mitochondrial components. Using cultured LS174T adenocarcinoma cells, we found that subcellular distribution of Zn-porphyrins is directed by the nature of the substituents attached to the meso pyridyl nitrogens at the porphyrin ring. Increasing the length of the aliphatic chain from one carbon (methyl) to six carbons (hexyl) increased mitochondrial uptake of the compounds. Such modifications also affected sub-mitochondrial distribution of the Zn-porphyrins. The amphiphilic hexyl derivative (ZnTnHex-2-PyP) localized in the vicinity of cytochrome c oxidase complex, causing its inactivation during illumination. Photoinactivation of critical cellular targets explains the superior efficiency of the hexyl derivative in causing mitochondrial photodamage, and suppressing cellular respiration and survival. Design of potent photosensitizers and redox-active scavengers of free radicals should take into consideration not only selective organelle uptake and localization, but also selective targeting of critical macromolecular structures.